2003
DOI: 10.1007/978-3-540-39867-7_77
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Power Saving Scheme for IEEE 802.11 DCF Based Wireless Networks

Abstract: Abstract. Providing energy efficiency in MAC (Medium Access Control) layer, while achieving desirable throughput, is an important research issue in the area of wireless networking. A wireless LAN such as IEEE 802.11 using the Distributed Coordination Function (DCF) also provides a mechanism for power conservation which allows each node to "sleep" for some amount of periods, but also requires the nodes to wake up periodically and stay "awake" for a certain duration called the ATIMWindow. In this paper, we propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Synchronous MAC protocols (such as S-MAC [8], T-MAC [9], IEEE 802.11 PSM [10]) have all nodes in the neighborhood wake up at the same time. Nodes achieve and maintain this synchronization by periodically exchanging schedule information among the neighbors.…”
Section: Leveraging Redundancy To Reduce Delay In Duty-cycled Netmentioning
confidence: 99%
“…Synchronous MAC protocols (such as S-MAC [8], T-MAC [9], IEEE 802.11 PSM [10]) have all nodes in the neighborhood wake up at the same time. Nodes achieve and maintain this synchronization by periodically exchanging schedule information among the neighbors.…”
Section: Leveraging Redundancy To Reduce Delay In Duty-cycled Netmentioning
confidence: 99%
“…It improved energy efficiency without degrading throughput, and they revealed that highly loaded network may cause low throughput per energy unit because of the extra use of channel capacity for ATIM Window. TIPS (Traffic Indication-based Power Saving) [4) is another approach to prolong the doze state. lt allows the beacon transmission to indicate the presence of following ATIM, thus nodes to go to sleep early.…”
Section: Related Workmentioning
confidence: 99%
“…However, packet delivery rate may degrade because of the asynchrouns and fewer coincidence, and become more critical in the case of broadcasting. In this paper, we assume that the nodes are fully synchronized as assumed in [2][3] [4].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In TIPS [13], the ATIM window is divided into two slots. If a beacon packet is received during the first slot, it indicates that nodes should stay on to receive ATIMs later in the ATIM window.…”
Section: Related Workmentioning
confidence: 99%